Guaiane sesquiterpenes from Lindera glauca: isolation, structural elucidation, and hepatoprotective effect - Lan-Lan Nie; Xin-Yu Sun; Qing Shi; Ya-Nan Duan; Jia-Yun Yang; Jin-Chang Huang; Xin-Wen Zhang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2026)

Study on the mechanism of action of lotus root insoluble dietary fiber compounded with puerarin in regulating gut microecology to alleviate hyperlipidemia model rats - Longyan Ding; Huiyang Tang; Yanju Liu; Qian Liu; Siyi Li; You Lv; Lan Sun; Xinglu Cheng; Xiaoya Li; Yueying Wu; Jiali Yuan; Bo Qiao (Bioactive Carbohydrates and Dietary Fibre, 2026)

Dual regulatory roles and mechanisms of Gamma delta T cells in organ fibrosis - Yongrong Li; Mingli Chen; Chaochao Chen; Dongchun Liang; Deming Sun; Zhoutao He; Cheng Lan (Tissue and Cell, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Hydroclimatic dynamics over the western Tibetan Plateau since the Last Glacial Maximum: A critical review - Kashif Hayat; Jianghu Lan; Peng Cheng; Haoran Li; Xingxing Liu; Jiansen Li; Xiaohui Wu; Long Pan; Dexiang Gan; Hong Yan; Youbin Sun (Earth-Science Reviews, 2026)

Mechanically gated piezoresistive sensors with near-zero standby power for wearable electronics - Peiwen Li; Shenglong Wang; Yue Sun; Yunshu Yang; Yong Ao; Boling Lan; Zihan Wang; Tingting Zhou; Longchao Huang; Hongguang Li; Jinlong Sun; Yu Zeng; et al. (Chemical Engineering Journal, 2026)

A phase-matched flexible PVDF ultrasonic transducer for efficiently powering implantable bioelectronics - Jinlong Sun; Boling Lan; Shenglong Wang; Hongguang Li; Tianpei Xu; Longchao Huang; Peiwen Li; Wei Zhao; Yong Ao; Long Jin; Wei Zhu; Weiqing Yang; et al. (Chemical Engineering Journal, 2026)

A conditional generative diffusion model enables joint retrieval of rice LAI and LCC - Heguang Sun; Huanming Mai; Bo Han; Yi Zhang; Zhongyu Jin; Changsheng Li; Wenqian Tang; Zifan Shen; Ziheng Feng; Xiaoyu Song; Yubin Lan; Wen Du; et al. (Computers and Electronics in Agriculture, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Enhancing wheat yield through improved sowing uniformity in China: A meta-analysis - Peiyin Jia; Jing-Wei Fan; Xin-Mao Li; Chu-Yi Sun; Jairo A. Palta; Hong Zhao; Wen-Yuan Luo; Lan Yang; Jian Zhang; Feng-Min Li; Yan-Lei Du (Field Crops Research, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Facile synthesis of a two-dimensional magnetic nickel-titanium polyphthalocyanine and its study in phosphopeptide enrichment - Dandan Jiang; Lan Lan; Yangyang Li; Yang Sun (Analytica Chimica Acta, 2026)

Assimilatory sulfate reduction potential in the plastisphere microbiome is linked to plastic mineralization in sulfur-rich mining-impacted river sediments - Tianle Kong; Zhili Du; Jianhua Zhou; Zhihao Zheng; Jian Zhang; Shui Zhang; Feng Jiang; Xiaoxu Sun; Wei Huang; Ruijian Zhang; Fangbai Li; Wenjie Lin; et al. (Water Research, 2026)

Spatiotemporal variations and factors associated with surface urban heat islands in South Asia - Linan Sun; Longjue He; Haojie Liu; Peng Kang; Lan Wang; Jvjie Jia; Yuanzheng Li (Urban Climate, 2026)

Platelet-based biomimetic nanoparticle-loaded hydrogels targeting tumor angiogenesis and cancer stem cells to prevent postoperative hepatocellular carcinoma recurrence - Zhe Li; Jinshuai Lan; Liyan Sun; Zhijun Bi; Wenlong Nie; Minquan Zhang; Dan Hu; Tong Zhang; Yue Ding (Chemical Engineering Journal, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A comparative study on the effects of cold plasma and high-voltage electrostatic fields in assisting the near-freezing temperature storage of goji berries - Lan Chen; Jianyu Liu; Haifen Wang; Yanlong Sun; Lingfu Kong; Meijun Wang; Wenqiang Guan; Limei Li; Songsong Zhao (Postharvest Biology and Technology, 2026)

Identification of COSR1 and COSR2 as hypoosmotic-activated Ca2+-permeable channels that are critical for submergence tolerance and post-drought recovery in Arabidopsis - Zebin Liu; Qi Niu; Yuxin Dong; Menghao Xu; Jianghao Wu; Lei Gao; Changxin Feng; Yujia Sun; Jiaxuan Zhang; Dongdong Kong; Liangyu Liu; Qifei Gao; et al. (Molecular Plant, 2026)

Kinetics research on the synergistic decomposition of scheelite with sulfuric-hydrochloric mixed acid - Xianbao Lan; Jigang He; Jiajun Zhu; Yuqing Qiu; Xingyu Chen; Ailiang Chen; Xuheng Liu; Jiangtao Li; Fenglong Sun; Zhongwei Zhao (Minerals Engineering, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Organophosphate esters accumulation induces ovarian dysfunctions: From epidemiological evidence to the exploration of ferroptosis mechanism - Zhihao Fan; Chengzi Huang; Xiaoli Fan; Huihui Li; Zhiwei Li; Xiao Guo; Jin Liu; Yue Sun; Lan Chao (Chemico-Biological Interactions, 2026)

Correction to: Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress‑induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Toughening mechanism and crack resistance of hybrid fiber low-carbon coral aggregate concrete - Li Sun; Xingyi Chen; Chuang Li; Shihang Lan (Innovative Infrastructure Solutions, 2026)

Synergistic role of microbial osmoregulation and electron transfer on enhancing high-salinity battery discharge wastewater treatment under electrochemical stimulation - Yongsen Shi; Zhinan Zheng; Yanyan Jia; Lan Tang; Haoting Quan; Kewen Li; Tianwei Hao; Lianpeng Sun; Hui Lu (Water Research, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Microbial biodegradation of polyethylene in estuarine sediments: metabolic pathways of Pseudomonas under denitrifying conditions - Zhiyuan Lin; Xiaoxu Sun; Zexin Wang; Duanyi Huang; Tianle Kong; Wei Huang; Baoqin Li; Zewen Tan; Fei Huang; Xiaolong Lan; Wenjie Lin; Guangjie Chen; et al. (Journal of Hazardous Materials, 2026)

Metal feed additives fuel the spread of antibiotic resistance genes in livestock manure - Wenshan Yang; Mengying Qian; Jianing Wang; Yufei Wang; Ziyi Zhang; Lan Jiang; Guangdong Wang; Bintao Li; Wenyan Wang; Zhouzheng Ren; Xiaojun Yang; Jie Gu; et al. (Journal of Environmental Sciences, 2026)

Research progress on hydration-mass transfer characteristics and selective regulation mechanism of CH4/CO2 hydrate formation - Xuemin Zhang; Xinying Lan; Xuemei Hu; Yang Cao; Jinping Li; Huan Sun; Qingbai Wu; Peng Zhang (Fuel, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Biochar and Sulfur Reduce Cadmium Toxicity in Rice by Altering Cadmium Speciation: Roles of Soil DOC, Organic Acids, and Microorganisms - Xiaoxue Sun; Yi Zhang; Jianfei Yang; Han Li; Yu Lan; Zunqi Liu; Tianyi He (Journal of Soil Science and Plant Nutrition, 2026)

Effect of Multisize Polypropylene Fibers on Uniaxial Compression Properties and Microstructure of Sea-Sand Coral Concrete - Li Sun; Shihang Lan; Chao Wang (Journal of Ocean University of China, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Nutrient input of coastal aquaculture may affect growth of mangrove following intermediate disturbance hypothesis: critical thresholds and spatial relationship coupling - Haonan Li; Haitao Chen; Longtian Huang; Chunxiang Liu; Jin Luo; Haoyu Wang; Mengji Zhang; Xiuqiong Liang; Yongze Xing; Wenlu Lan; Xiaoyan Peng; Sheng Fang; et al. (Marine Pollution Bulletin, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Size-dependent graphene oxide sheets as a mechano-active carrier for BMP enhances fracture healing via augmenting MSC recruitment - Lan Yang; Sujing Sun; Xindai Chang; Xingzhao Liu; Yipu Li; Chenyan Li; Wanyue Yin; Linsheng Zhan; Qianqian Zhou; Xiaohui Wang (Chemical Engineering Journal, 2026)

Comprehensive performance tests and evaluations of the slope protection effect of lignin and guar gum-modified loess - Zhouchen Li; Hengxing Lan; Weifeng Sun; Hao Zhang; Shijie Liu; Han Bao; Changgen Yan; Langping Li (Bulletin of Engineering Geology and the Environment, 2026)

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

Vibration mitigation for high-rise buildings by a single-sided vibro-impact bistable nonlinear energy sink - Jiang Li; Bo-Xun Sun; Gui-Lan Yu (Soil Dynamics and Earthquake Engineering, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Biomass models, allometric relationships, and carbon sink of Sargassum henslowianum in Nan'ao Island - Jing Chen; Jinhuai Ni; Hong Du; Kai Zong; Sunzhaocong Lan; Jianpeng Lu; Dejun Feng; Xu Yang; Guangyang Zhang; Lili Mei; Yuanmin Sun; Xunmeng Li (Regional Studies in Marine Science, 2026)

Pigment and transcriptome profiling of flesh yellowing during post-ripening of ‘Puyu’ kiwifruit - Tian Lan; Shihan Bao; Xinyi Li; Min Zhang; Wen Peng; Mukesh Kumar Awasthi; Xiangyu Sun; Tingting Ma (Postharvest Biology and Technology, 2026)

Tourmaline with an inherent electric field enhances electrochemical lithium extraction from low-quality brines - Jiangju Si; Lifang Yang; Jihong Lan; Jie Yang; Tengyu Jiang; Zhikun Li; Ningbo Sun; Zhenyu Niu; Shanfu Lu; Yan Xiang (Chemical Engineering Journal, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Unraveling metal-organic frameworks impact on resistome and virome dynamics in swine manure anaerobic digestion via metagenomic - Li Zhang; Lan Jiang; Ziyi Zhang; Yufei Wang; Chengcheng Yao; Kunru Yu; Hanxiang Tao; Wei Sun; Xunyang He; Jie Gu; Xun Qian (Journal of Environmental Management, 2026)

Estimation of global riverine total phosphorus concentration based on multi-source data and stacked ensemble learning - Qi Li; Lan Zhang; Xi Chen; Chen Zhang; Jingyi Tian; Xianghan Sun; Liqiao Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Characteristics and comparative genomic analysis of Clostridium perfringens isolates from a foodborne outbreak - Jiwei Liang; Juping Shi; Lan Xu; Yun Li; Keer Xia; Lu Sun; Qingli Dong; Yeru Wang; Xiang Wang (International Journal of Food Microbiology, 2026)

Nitrogen-phosphorus co-doped carbon layer-confined ultra-thin self-grown polyphase molybdates heterojunction nanosheet arrays for efficient water splitting - Lan Zhang; Rao Fu; Ke Chen; Xi Peng; Li Zhang; Minglei Yan; Chun Wu; Mengmeng Sun; Gehong Su; Yanying Wang; Jianshan Ye; Hanbing Rao; et al. (Fuel, 2026)

Structural interactions and transcriptional regulation by caffeic acid against multidrug-resistant Vibrio species: Mechanistic insights and efficacy in shrimp - Rulin Jin; Danyang Liu; Saiya Li; Jiayi Zhao; Yong Zhao; Weiqing Lan; Xiaohong Sun (Food Chemistry, 2026)

Analysis of the preservation effect of HVEF combined with LSPC on catfish fillets and changes in microbial community and biogenic amine production during the preservation process - Yali Li; Mengting Chen; Kai Hu; Zhida Sun; Sheng Chen; Lang Chen; Xiaojia Guo; Wenjin Wu; Guangquan Xiong; Liu Shi; Lan Wang (Food Control, 2026)

Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress-induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Soil bacterial community and vanadium fate shaped by co-exposure to polyethylene microplastics and native vanadium pollution - Shanshan Zhao; Lan Li; Jianing Sun; Jingyu Hu; Wu Liu; Xin Cheng; Dan Zhou; Bo Cheng (Applied Soil Ecology, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Research on active control of vibration sound radiation of typical stern hull structures - Hui Wang; Zeyang Li; Yaxiang Sun; Xin Lan; Libo Qi; Hao Li; Yanju Liu; Jingsong Leng (Ocean Engineering, 2026)

Integration of AD and pyrolysis for char fertilizer: Pyrolysis and nutrient characteristics of biogas residue at different fermentation degrees - Lan Mu; Kongyue Li; Yifan Wang; Biyu Wang; Zhanjun Cheng; Yunan Sun; Yingjin Song; Guanyi Chen (Biomass and Bioenergy, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

PLD3-mediated Mitophagy Attenuates Neuronal Ferroptosis and Promotes Functional Recovery after Spinal Cord Injury - Xintian Ding; Bin Dai; Jiafeng Peng; Kenan Sun; Shaoze Lan; Liu Yang; Canming Ye; Shenglong Pan; Chen Wang; Xinyu Liang; Ciren Lunzhu; Chun Chen; et al. (Molecular Neurobiology, 2026)

Evolution characteristics of bedding-perpendicular joints development in soft-hard interbedded strata considering interface morphology: a case study of the Ordos Basin, China - Xiaoguang Li; Han Bao; Hengxing Lan; Changgen Yan; Sun Qiang; Weifeng Sun; Shijie Liu (Bulletin of Engineering Geology and the Environment, 2026)

LD-110, a potent LSD1 PROTAC degrader, suppresses tumor growth by inducing ER stress and apoptosis - Danyi Zhai; Jiezhen Zhuo; Yudong Yin; Lan Li; Mengting Liang; Xin Zhou; Lihua Liu; Liangzhen Chen; Xiufang Xiong; Qing Yu; Xin Han; Yi Sun (Science Bulletin, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Elegance in simplicity: Hollow mesoporous silica inhibits pyraclonil metabolism to boost its herbicidal efficacy on Echinochloa crus-galli - Tangqi Feng; Lan Wu; Tianhong Lei; Wenjing Sun; Jian Wang; Dong Cheng; Li Liu; Pengjia Tang; Wenzhuo Wang; Shun He; Hongju Ma (Chemical Engineering Journal, 2025)

Harnessing Plant Essential Oils to Combat Acinetobacter baumannii: Research Progress in Antimicrobial Mechanisms and Therapeutic Prospects - Shu-Yun Wei; Yu Sun; Qing Lu; Zhen Liang; Tao Zhu; Yu-Long Li; Ding-Hui Xu; Cai-Ying Li; Feng-Lan Feng; Hong Zeng (Current Microbiology, 2025)

Implementing transfer learning for citrus Huanglongbing disease detection across different datasets using neural network - Deyao Huang; Kangsong Xiao; Hairong Luo; Biyun Yang; Shiying Lan; Yutong Jiang; You Li; Dapeng Ye; Dawei Sun; Haiyong Weng (Computers and Electronics in Agriculture, 2025)

A new technique for glycosylation modification of soy protein isolates using magnetically induced electric field: focus on structure and gel properties - Xinnan Li; Yuhan Lan; Lina sun; Sitong Wu; Xibo Wang; Ning Xu (Journal of Food Engineering, 2025)

Regulating the charge transport ability of the TiO2/CsPbI2Br perovskite interface layer by MoS2 nanoparticles for high-performance carbon-based all-inorganic perovskite solar cells - Zhaowei Huang; Lin Gao; Fengli Liu; Shihui Xu; Yaxuan Chai; Jing Li; Qing Yao; Haozhen Deng; Liuxue Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2025)

Profiling Interactions Between Bicyclol and SLC/ABC Transporters: Advancing Clinical Safety and Efficacy in Combination Therapy - Wanting Bai; Yang Li; Feng You; Xiaoyan Duan; Jiahuan Hu; Jinjin Wu; Tao Sun; Xing Wang; Pei Lan; Jinping Hu (Pharmaceutical Research, 2025)

Integrative scATAC-seq and mtDNA mutation analysis reveals disease-driven regulatory aberrations in AML - Chen Tian; Yijun Dong; Xin Sun; Longchen Xu; Xiaoli Ma; Yuwei Tao; Fang Wang; Haohang Zhang; Jie Li; Kun Li; Yasong Chen; Hongxing Liu; et al. (Science Bulletin, 2025)

Unravelling heavy metal releases from municipal solid waste incineration fly ash: Multi-parameter leaching behaviour, ecological risk prediction models and integrated stabilisation strategies - Sun Mingyi; Ma Liping; Yang Jingxian; Dai Quxiu; Yang Jie; He Binbin; Xie Longgui; Liu Yongqing; Hu Yao; Duan Li; Zhou Guanyun; Luo Yuetao; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic immobilization of heavy metals in hospital waste incineration bottom ash via carbide slag-amplified accelerated carbonation - Ning Feng; Liping Lan; Mei Yang; Wenxin Ji; Yulong Ma; Yonggang Sun; Yuanyuan Li (Journal of Environmental Chemical Engineering, 2025)

The role of iron competition in the antagonistic action of Metschnikowia pulcherrima against three major pathogenic fungi on postharvest citrus fruit - Shupei Wang; Chenshu Wang; Wenqing Liu; Fangxue Hang; Meilan Chen; Zhijuan Zhao; Dongqing Ye; Li Li; Lan Zhang; Xuemei He; Jian Sun (International Journal of Food Microbiology, 2025)

Two novel Vibrio parahaemolyticus phages (vB_VpaS_1601 and vB_VpaP_1701) can serve as potential biocontrol agents against Vibrio parahaemolyticus infection in seafood - Zhenxiang Tao; Yue Sun; Mengxiao Zhou; Tengteng Li; Weiqing Lan; Yong Zhao; Xiaohong Sun (International Journal of Food Microbiology, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Characteristics and source tracing of pollution in soil and groundwater of a retired coking plant in Shanxi Province - Jiabin Wang; Yayun Xiang; Xiaodong Li; Jialun Shen; Zongquan Sun; Zhaoyue Liu; Lan Yang; Huan Yang; Hejing Wang; Hong Chang; Fujun Ma (Environmental Pollution, 2025)

ML-AMP1 as a Potential Antifungal Agent: Activity and Therapeutic Evaluation in a Guinea Pig Model of Dermatophytosis - Shaojie Zhang; Yiqing Sun; Kedong Yin; Jinhua Zhang; Lan Zhang; Yufeng Yang; Yuhan Wang; Ruifang Li (International Journal of Peptide Research and Therapeutics, 2025)

Characterization of Cyhalofop-butyl metabolism and identification of resistance genes in Barnyardgrass (Echinochloa crus-galli (L.) P. Beauv.) - Penglei Sun; Liangliang Niu; Xianmin Lan; Pingping Chen; Haiyan Yu; Jingchao Chen; Hailan Cui; Xiangju Li (Pesticide Biochemistry and Physiology, 2025)

Unraveling the diversity and heterogeneity of cyanobacterial assemblages of biocrusts in the Horqin Sandland, Inner Mongolia - Yuqi SUN; Wei XING; Sarah S.A. ALSAIF; Abdullah A. SABER; Yuanlong LI; Li WU; Shubin LAN (Pedosphere, 2025)

Integrated multi-omics analysis uncovers Zearalenone-induced ovarian and intestinal inflammation is mediated by the tumor necrosis factor-α - Fa-Li Zhang; Ai-Ying Li; Ke-Xin Zhu; Kai Zhang; Zhe Tian; Tao Wang; Xin-Hao Zhang; Jian Zang; Xiao-Feng Sun; Wei Shen; Lan Li (Journal of Hazardous Materials, 2025)

“One-two punch” strategy: A H2O2 self-sufficient nanosystem for efficient cervical cancer therapy via senescence induction and clearance - Lan Yu; Weiqiang Han; Jing Zhang; Guoxin Liu; Hongjuan Li; Yongqian Xu; Fengyu Liu; Shiguo Sun (Chemical Engineering Journal, 2025)

Climate-corrected modeling of biomass burning in Equatorial Asia: the roles of climate change and anthropogenic control - Shuai Yin; Chong Shi; Dabin Ji; Huazhe Shang; Nan Li; Zhongyi Sun; Tangzhe Nie; Kunpeng Yi; Meng Guo; Xin Zhao; Lan Wu; Xinlu Liu (Climatic Change, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Occurrence, ecology and health risk assessment of organophosphate triesters and diesters in surface and ground water from southwest of China - Tianyang Lan; Li Zhao; Jie Xiong; Ruonan Wang; Ping Yang; Weiyi Sun; Shijun Su; Zhiwei Gan; Zhiren Tian (Environmental Research, 2025)

Using fluorescence spectroscopy of DOM as an indicator of human-derived pollution: a case study in the Chongqing-Three Gorges section of the Yangtze River - Lan Yang; Xiaofeng Gao; Yutong Xie; Jian Sun; Lei Li; Lingzhi Tan; Yilu Gu (Environmental Pollution, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Network pharmacology analysis and animal experiment validation of inflammation inhibition by Swertiamarin in treating Ulcerative colitis - Tang Jiafeng; Wang Lijuan; Wei Lan; You Yiqing; Yang Shiyu; Zeng Tao; Dang Tingting; Sun Haoli; Li Xiaoshan; Zhang Yan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A novel Zn2+ probe for fluorescent monitoring of drug and E6/E7 protein interaction in living cells - Zhenzhen Xie; Lan Yu; Zuoping Li; Na Zhao; Shiwan You; Zhihao Zhao; Jindi Dou; Xiling Deng; Shiguo Sun (Analytica Chimica Acta, 2025)

Correlating microbial diversity patterns with V and Cr in blast furnace slag contaminated soil - Xin Cheng; Shanshan Zhao; Lan Li; Jianing Sun; Bolin Shao; Yi Huang; Bo Cheng (Science of The Total Environment, 2025)

Risk prioritization and experimental validation of per- and polyfluoroalkyl substances (PFAS) in Chaohu Lake: Based on nontarget and target analyses - Wei Chang; Shen-Dong Xu; Ting Liu; Lan-Lan Wu; Si-Ting Liu; Gang Liu; Jian Sun; Ye-Xin Luo; Lei Gao; Hao Li; Qi Lu; Zhi Yuan; et al. (Journal of Hazardous Materials, 2025)

Unraveling stress responses of microalgal-bacterial granular sludge when treating ciprofloxacin-laden wastewater - Lan Tang; Chuanyan Zhuang; Peng Qi; Xiaojing Yang; Meng Yan; Fan Li; Qiujin Deng; Lianpeng Sun; Hui Lu (Journal of Hazardous Materials, 2025)

Unveiling the impact of high hydrostatic pressure on bighead carp proteins: Insights from protein structure, peptidomics, and bioinformatics - Mengting Chen; Mengjiao Li; Zhida Sun; Kai Hu; Wenjin Wu; Liu Shi; Aimin Ma; Lan Wang (Innovative Food Science & Emerging Technologies, 2025)

Non-destructive prediction of the moisture content of individual wheat kernels combining hyperspectral imaging and WGAN data augmentation algorithm - Dianyang Sun; Li Zhang; Haitao Li; Weijie Lan; Kang Tu; Jun Liu; Leiqing Pan (Food Research International, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Corrigendum to ‘Biochar-amended constructed wetlands enhance sulfadiazine removal and reduce resistance genes accumulation in treatment of mariculture wastewater’ [Environ. Res., Volume 273 (2025) 121161] - Yuan-yuan Gao; Yu-xin Wu; Wang-chao Chu; Li Lai; Jia-hao Sun; Lin-lan Zhuang; Fei-fei Liu (Environmental Research, 2025)

Spatial retention, absorption, transport, and enrichment of microplastics in mangrove sediment complex system - Xiuqiong Liang; Chunxiang Liu; Haoyu Wang; Haonan Li; Jin Luo; Gang Luo; Wei Hu; Wenlu Lan; Leishi Wu; Sheng Fang; Yan Tian; Xiang Sun (Environmental Pollution, 2025)

Phenomenon of white superevaporation of water and its application for enhancing energy efficiency in dark/solar water purification, power generation, and generative AI - Ranran Fang; Yi Li; Jiangen Zheng; Zhonghua Yan; Nana Pan; Xiang Chen; Xi Zhao; Quan Chen; Yongyi Deng; Zeyu Sun; Lan Yang; Anatoliy Y. Vorobyev (Desalination, 2025)

Comprehensive study on the cracking of n-heptane to produce olefins under flue gas atmosphere: Thermodynamics and kinetics - Hui Zhang; Haowen Li; Hao Lan; Yonghui Sun; Weigang Zhang; Shijun Liu; Xiaohan Wang (Chemical Engineering Journal, 2025)

Pattern and dynamics of ecological vulnerability in the upper reach of Yellow River - Yunhui Li; Ruowei Li; Tiancai Zhou; Jian Sun; Yuchuan He; Xiangyu Lan; Zhe Chen (Journal of Mountain Science, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Biochar-amended constructed wetlands enhance sulfadiazine removal and reduce resistance genes accumulation in treatment of mariculture wastewater - Yuan-yuan Gao; Yu-xin Wu; Wang-chao Chu; Li Lai; Jia-hao Sun; Lin-lan Zhuang; Fei-fei Liu (Environmental Research, 2025)

Investigating the mechanisms of flucarbazone-sodium resistance in Bromus japonicus Thunb - Yuning Lan; Xinhui Xue; Hailan Cui; Ruolin Wang; Ying Sun; Hongjuan Huang; Shouhui Wei; Xiangju Li; Zhaofeng Huang (Plant and Soil, 2025)

Correction to: Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Hyaluronic acid-modified milk exosomes carrying ZNF516 inhibit ABCC5 and contribute to pemetrexed sensitivity in lung adenocarcinoma - Hui Li; Yanyan Sun; Jue Wang; Zhiwu Wang; Lan Wu; Jie Lei; Ying Gao (Human Cell, 2025)

Metabolite profiling and ‘dryness’-like effect analysis of ‘Chenpi’ plant tea (Citri Reticulatae Pericarpium peel) with and without steaming peocessing - Zhenwei Lan; Xiaoting Zhang; Xinhang Cai; Weijie Pan; Wangjun Li; Yue Sun; Shumei Wang; Xingyang Xue; Menghua Wu; Jiang Meng (Food Research International, 2025)

Vegetation-induced modifications in hydrological processes and the consequential dynamic effects of slope stability - Zhichao Deng; Hengxing Lan; Langping Li; Weifeng Sun (CATENA, 2025)

Pilot work of the 10K Chinese People Genomic Diversity Project along the Silk Road suggests a complex east-west admixture landscape and biological adaptations - Guanglin He; Hongbing Yao; Shuhan Duan; Lintao Luo; Qiuxia Sun; Renkuan Tang; Jing Chen; Zhiyong Wang; Yuntao Sun; Xiangping Li; Liping Hu; Libing Yun; et al. (Science China Life Sciences, 2025)

Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

How can ecosystem services trade-offs/synergies help select the optimal cultivated land restoration pattern? A study based on multi-scenario simulations - Xian Zhao; Wei Sun; Shiqin Zhang; Yinan Yang; Yixuan Yang; Hailian Lan; Tao Yu; Xiangyun Li; Yujing Xie (Applied Geography, 2025)

Phase transition kinetics and mass transfer characteristics of CO2 hydrate formation process under geological storage conditions: A comprehensive review - Xuemin Zhang; Hongbin Song; Wenxin Dong; Xinying Lan; Tao Shan; Jinping Li; Huan Sun; Wenqiang Cui; Qingbai Wu (Journal of Cleaner Production, 2025)

Exploring the anti-inflammatory potential of Lacticaseibacillus paracasei postbiotics: Mechanistic insights and functional components - Yuhang Sun; Zhe Sun; Bing Fang; Ran Wang; Yue Liu; Jingyu Li; Hanglian Lan; Wen Zhao; Wei-Lian Hung; Ming Zhang (Food Bioscience, 2025)

Corrigendum to “Maternal ochratoxin A exposure impairs meiosis progression and primordial follicle formation of F1 offspring” [Food and Chemical Toxicology 168 (2022) 113386] - Yue Song; Jinxin Zhao; Tian Qiao; Lan Li; Dachuan Shi; Yonghong Sun; Wei Shen; Xiaofeng Sun (Food and Chemical Toxicology, 2025)

Legacy effects of grazing and nitrogen fertilization on soil carbon, nitrogen and phosphorus in an alpine meadow on the Qinghai-Tibetan Plateau - Lan Li; Xiong Zhao He; Yi Sun; Tianhao Xiao; Yang Liu; Fujiang Hou (European Journal of Soil Biology, 2025)

Unbalanced valence state cation substitution induced color centers in lead-free perovskite hetero-crystals enabling photoelectric response exceeding 1300 nm - Yan Liu; Yawen Li; Weipeng Lu; Tianyu Lan; Zhuoying Chen; Weihua Ning; Yusheng Wang; Baoquan Sun (Chemical Engineering Journal, 2025)

Cdh23 Gene Mutation–Induced Vestibular Dysfunction in Mice: Abnormal Stereocilia Bundle and Otolith Development and Activation of p53/FoxO Signaling Pathway - Lihuan Tang; Yuancheng Wu; Kai Zhang; Daoli Xie; Xiaojing Kuang; Lan Wang; Zehua Sun; Ruishuang Geng; Juan Hu; Yan Sun; Tihua Zheng; Bo Li; et al. (Journal of Molecular Neuroscience, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Corrigendum to “Maternal Zearalenone exposure impacted ovarian follicle formation and development of suckled offspring” [Sci. Total Environ. 788 (2021) 147792] - Li Kong; Ai-Hong Zhao; Qian-Wen Wang; Yan-Qin Feng; Zi-Hui Yan; Ming-Hao Li; Fa-Li Zhang; Han Wang; Kai-Yu Shen; Ying Liu; Yu-Jiang Sun; Wei Shen; et al. (Science of The Total Environment, 2025)

Flow duration curve prediction: A framework integrating regionalization and copula model - Tian Lan; Jiajia Zhang; Huanhuan Li; Hongbo Zhang; Xinghui Gong; Jing Sun; Yongqin David Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

Flavor characteristics and formation mechanisms in spirits: A case study in whisky - Qiuyu Zhang; Dan Wang; Xiaogang Liu; Yugen Li; Jinyuan Sun; Nan Meng; Zhe Ji; Yu Lan; Xiaonian Cao; Baoguo Sun; Jinchen Li (Food Research International, 2025)

Discrimination of unsound soybeans using hyperspectral imaging: A deep learning method based on dual-channel feature fusion strategy and attention mechanism - Dianyang Sun; Li Zhang; Haitao Li; Weijie Lan; Kang Tu; Jun Liu; Leiqing Pan (Food Research International, 2025)

Fraxetin inhibits IKKβ, blocks NF-κB pathway and NLRP3 inflammasome activation, and alleviates spleen injury in sepsis - Liwei Huangfu; Jing Wang; Da Li; Haiyang Fei; Xuan Chen; Jingquan Dong; Lan Sun (Chemico-Biological Interactions, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Reverse Size Effect of the Unconfined Compressive Strength of Crystalline Rock: A Grain-Scale Perspective - Qinyuan Liang; Hengxing Lan; Yu Zhou; Bo Li; Weifeng Sun; Shijie Liu; Wenjun Lv (Rock Mechanics and Rock Engineering, 2025)

Grazing disturbance reduces biocrust-related cyanobacteria and N-fixer abundance but increases bacterial diversity: Implications for biocrust restoration in degraded drylands - Yue Li; Yuqi Sun; Longkat Ayuba Gufwan; Li Wu; Shubin Lan (Agriculture, Ecosystems & Environment, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Exogenous additives reshape the microbiome and promote the reduction of resistome in co-composting of pig manure and mushroom residue - Li Zhang; Lan Jiang; Wenjing Yan; Hanxiang Tao; Chengcheng Yao; Lu An; Yifan Sun; Ting Hu; Wei Sun; Xun Qian; Jie Gu (Journal of Hazardous Materials, 2025)

Structural analysis and accelerating wound healing function of a novel galactosylated glycosaminoglycan from the snail Helix lucorum - Ya Li; Xingzi Wang; Jiangyan Chen; Luyun Sun; Debing Pu; Lisha Lin; Lan Luo; Xi Gong; Junxue Pu; Mingyi Wu (Carbohydrate Polymers, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Abnormal upregulation of NUBP2 contributes to cancer progression in colorectal cancer - Danfeng Lan; Junyu Wang; Guishun Sun; Lixia Jiang; Qiyun Chen; Sha Li; Haiyan Qu; Yibo Wang; Bian Wu (Molecular and Cellular Biochemistry, 2025)
Colorectal cancer (CRC), a digestive tract malignancy with high mortality and morbidity, lacks effective biomarkers for clinical prognosis due to its complex molecular pathogenesis. Nucleotide binding protein 2 (NUBP2) plays a vital role in the assembly of cytosolic Fe/S protein and has been implicated in cancer progression. In this study, we found that NUBP2 was highly expressed in CRC by TCGA database analysis. Subsequently, we verified the expression of NUBP2 in CRC tumor tissues and para-carcinoma tissues using IHC staining, and further investigated its association with clinicopathological parameters. In vitro cell experiments were conducted to assess the role of NUBP2 in CRC by evaluating cell proliferation, migration, and apoptosis upon NUBP2 dysregulation. Furthermore, we established a subcutaneous CRC model to evaluate the impact of NUBP2 on tumor growth in vivo. Additionally, we performed mechanistic exploration using a Human Phospho-Kinase Array-Membrane. Our results showed higher expression of NUBP2 in CRC tissues, which positively correlated with the pathological stage, indicating its involvement in tumor malignancy. Functional studies demonstrated that NUBP2 knockdown reduced cell proliferation, increased apoptosis, and impaired migration ability. Moreover, NUBP2 knockdown inhibited tumor growth in mice. We also observed significant changes in the phosphorylation level of GSK3β upon NUBP2 knockdown or overexpression. Additionally, treatment with CHIR-99021 HCl, an inhibitor of GSK3β, reversed the malignant phenotype induced by NUBP2 overexpression. Overall, this study elucidated the functional role of NUBP2 in CRC progression both in vitro and in vivo, providing insights into the molecular mechanisms underlying CRC and potential implications for targeted therapeutic strategies.

Deep learning-assisted detection of psychoactive water pollutants using behavioral profiling of zebrafish embryos - Ya Zhu; Lan Li; Shaokui Yi; Rui Hu; Jianjun Wu; Jinqian Xu; Junguang Xu; Qinnan Zhu; Shijia Cen; Yuxuan Yuan; Da Sun; Waqas Ahmad; et al. (Journal of Hazardous Materials, 2024)

Multi-dimensional profiles combined with antioxidant activity and fingerprint-efficacy relationship to analyze the quality of Astragali Radix from different sources - Mingjia Liu; Lili Lan; Gang Li; Guoxiang Sun (Food Chemistry, 2024)

Response of Potato Growth and Yield to Drought Scenarios Based on APSIM-Potato in the Single-Cropping Region in Northern China - Xin-Lan Luo; Yue Sun; Li-Min Liu; Li-Wei Wang; Xi-Ning Gao (Potato Research, 2024)

How the low-carbon city pilot policy reduces enterprise carbon emissions and paves the way for high-quality development: evidence from a quasi-natural experiment in China - Yuting Dong; Ziyuan Sun; Wen Li; Lan Wang (Environment, Development and Sustainability, 2024)

IP3R1 is required for meiotic progression and embryonic development by regulating mitochondrial calcium and oxidative damage - Chang Zhang; Xiaoqing Sun; Deyi Wu; Guoxia Wang; Hainan Lan; Xin Zheng; Suo Li (Theriogenology, 2024)

Long-term trend of dust event duration over Northwest China - Yang Wang; Haojie Yu; Lan Li; Jiayi Li; Jie Sun; Jinsen Shi; Jiming Li (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Sensitizing sorafenib to hepatocellular carcinoma with dual-targeted and pH-responsive nanodrugs via overcoming the hypoxia tumor microenvironment - Zhe Li; Jinshuai Lan; Ya Wu; Lixia Chen; Donghao Gu; Liyan Sun; Siqi Yang; Yi Shen; Tong Zhang; Yue Ding (Chemical Engineering Journal, 2024)

Polyimide-Coating-on-Aramid nanofiber strategy toward ultralight organic aerogels with multifunctional properties - Xiaolei Wang; Kunlong Zhao; Wenxin Cao; Dongchao Ji; Zhijie Ye; Zhenhua Su; Ge Gao; Zhuochao Wang; Chunqiang Sun; Yingqi Liu; Lan Zhang; Tianyu Zhang; et al. (Chemical Engineering Journal, 2024)

Uncovering chromatin accessibility and cancer diagnostic potential via cell-free DNA utilization - Jie Li; Jiahui Chen; Xin Sun; Heli Yang; Keyong Sun; Chang Liu; Yongwang Wang; Mengyue Xu; Xin Ji; Ji Zhang; Xiaojiang Wu; Anqiang Wang; et al. (Science Bulletin, 2024)

Maillard reaction products of hydrolyzed Copyinds comatus protein with various sugar-amino acid combinations: Focusing on their meaty aroma notes and salt reduction abilities - Xiao Chen; Ziyi Li; Weijie Lan; Hailan Sun; Kang Chen; Liyan Zhao (Food Bioscience, 2024)

Regulation of interface energy level alignment of perovskite solar cells by fullerene derivative of PCBM - Qingshui Zheng; Yu Zou; Yuhong Wang; Pengxu Chen; Fengxian Cao; Anling Tong; Ruowei He; Zhang Lan; Weihai Sun; Yunlong Li; Jihuai Wu (Chemical Engineering Journal, 2024)

Body temperature-triggered adhesive ionic conductive hydrogels for bioelectrical signal monitoring - Xuelan Li; Yue Sun; Shenglong Wang; Guo Tian; Tao Yang; Longchao Huang; Yong Ao; Boling Lan; Jieling Zhang; Tianpei Xu; Yang Liu; Long Jin; et al. (Chemical Engineering Journal, 2024)

Tuning Mg-Fe-O solid solutions towards optimized exsolution of active sites for thermal catalytic decomposition of methane - Jingxia Qian; Heping Li; Dongping Sun; Wei Shao; Qianwenhao Fan; Longgang Tao; Xianyue Wu; Lan Zhang; Siew Hwa Chan; Jean Marie Basset; Lu Zhou; Wen Liu (Chemical Engineering Journal, 2024)

Fault structures of the Haichenghe fault zone in Liaoning, China from high-precision location based on dense array observation - Qing-Shan Sun; Lan-Shu Bai; Liang Wang; Jiu-Yang Wang; Shi-Chao Yang; En-Lai Li (Journal of Seismology, 2024)

The receptor kinase OsANX limits precocious flowering and inflorescence over-branching and maintains pollen tube integrity in rice - Lan-Xin Zhang; Can-Can Shen; Ying-Xue Bai; Hao-Yue Li; Chen-Li Zhu; Chen-Guang Yang; Ammara Latif; Ying Sun; Cui-Xia Pu (Plant Science, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

Recognition of cross-regional loess water content based on machine vision: Case study of three regions - Yaozhong Zhang; Han Zhang; Hengxing Lan; Yunchuang Li; Dexin Sun; Erhao Wang; Zhonghong Dong (CATENA, 2024)

Metabolomics profile of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid-induced brain damage in Carassius auratus and its response to the intestinal microbial community - Xue Jiao; Ning Wang; Lei Guo; Zheng-yao Guo; Xian-wei Hou; Yu-qian Lu; Bao-lan Yao; Jia Sun; Yue-hong Li (Aquaculture, 2024)

Enhanced sinks of polystyrene nanoplastics (PSNPs) in marine sediment compared to freshwater sediment: Influencing factors and mechanisms - Lulu Sun; Yaru Li; Jing Lan; Yan Bao; Zongshan Zhao; Rongguang Shi; Xingchen Zhao; Ying Fan (Science of The Total Environment, 2024)

Identifying the possible driving mechanisms in Precipitation-Runoff relationships with nonstationary and nonlinear theory approaches - Tongfang Li; Tian Lan; Hongbo Zhang; Jing Sun; Chong-Yu Xu; Yongqin David Chen (Journal of Hydrology, 2024)

Analysis of pipeline leakage in unsaturated stratum: A new seepage-diffusion model - Yanshun Liu; Hao Yu; Xiao Zhang; Xiongdong Lan; Xianghui Li; Yuxue Sun; Zhanchao Yin (Tunnelling and Underground Space Technology, 2024)

Ecological effect of microplastics on soil microbe-driven carbon circulation and greenhouse gas emission: A review - Yaru Li; Fangwei Hou; Lulu Sun; Jing Lan; Zhanghua Han; Tongtong Li; Yiming Wang; Zongshan Zhao (Journal of Environmental Management, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Multiple Applications of a Novel Fluorescence Probe with Large Stokes Shift and Sensitivity for Rapid H2S Detection - Lai-Xin Hong; Le Sun; Cong Li; Rong-Lan Zhang; Jian-She Zhao (Journal of Fluorescence, 2024)

Microplastics shaped performance, microbial ecology and community assembly in simultaneous nitrification, denitrification and phosphorus removal process - Tong Wu; Jie Ding; Ying-Jun Zhao; Lan Ding; Yani Zang; Han-Jun Sun; Le Zhong; Ji-Wei Pang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Science of The Total Environment, 2024)

A waste extended input-output-based Transformer-LSTM method for analyzing hazardous waste reduction patterns: A case study of shanghai - Qian Zhou; Jicui Cui; Lan Wang; Shirui Sun; Hanyi Jiang; Jiyang Li; A.J.Y. Chen; Pingkuo Liu; Luochun Wang; Michael Palocz-Andresen; Yue Zhu; Ziyang Lou (Journal of Cleaner Production, 2024)

Inhibition mechanism of crude lipopeptide from Bacillus subtilis against Aeromonas veronii growth, biofilm formation, and spoilage of channel catfish flesh - Yali Li; Tianqi Wangjiang; Zhida Sun; Liu Shi; Sheng Chen; Lang Chen; Xiaojia Guo; Wenjin Wu; Guangquan Xiong; Lan Wang (Food Microbiology, 2024)

Role of rainfall temporal distribution on effective infiltration in the loess slope and prediction model - Gan Lin; Hengxing Lan; Ping Li; Langping Li; Shijie Liu; Weifeng Sun (Engineering Geology, 2024)

Enhanced biotoxicity by co-exposure of aged polystyrene and ciprofloxacin: the adsorption and its influence factors - Tongtong Li; Jing Lan; Yaoyao Wang; Lulu Sun; Yaru Li; Zongshan Zhao (Environmental Geochemistry and Health, 2024)

Dimeric eremophilane-type sesquiterpenoids from the peeled stems of Syringa pinnatifolia - Jingjing Sun; Anni Li; Shungang Jiao; Changxin Liu; Zefeng Zhang; Hongying Chen; Yana Liang; Xiaoli Gao; Lan Cao; Changcai Bai; Xingyun Chai (Phytochemistry, 2024)

One-pot fabrication of an efficient 3D porous SiC based monolithic catalyst for methanol steam reforming via a carbon encapsulation strategy - Zaizhe Cheng; Lingjie He; Xiucheng Sun; Yunzhi Li; Xianglei He; Guojun Lan; Yiyang Qiu; Ying Li (Chemical Engineering Journal, 2024)

0D bio-based carbon dots and 2D MXene hybridization toward fabricating flame-retardant, conductive and sensing cellulose fabrics - Lan Ding; Ling Sun; Jinke Yu; Yufei Cao; Xiaohui Liu; Yuanlin Ren; Yuesheng Li (Chemical Engineering Journal, 2024)

Geochemical and U-Pb isotopic insights into uranium (U) enrichment in the soil around a nuclear fuel element plant, in Southwest China - Xin Cheng; Jianing Sun; Kai Ling; Keyi Zhong; Bolin Shao; Lan Li; Shanshan Zhao; Yi Huang; Hao Song; Bo Cheng (Ore and Energy Resource Geology, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

Negative effect of industrial waste residue additives (IWRA) on NO reduction by selective non-catalytic reduction (SNCR) in cement plant: A comparison between copper slag and iron-ore slag - Su Zhang; Zhan Li; Jinyu Sun; Yili Zhang; Wei Xu; Weidong Cui; Lan Zhang; Xuebin Wang (Fuel, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

Efficient removal and transformation of Cr(VI) from alkaline wastewater to form a ferrochromium spinel multiphase via a modified ferrite process - Yingying Lan; Yiwei Sun; Shasha Chu; Bo Yang; Lijuan Zhang; Lin Xiao; Jinlin Li; Xiaochao Yuan; Xin Yan; Vladimir V. Galvita; Xintai Su (Chemosphere, 2024)

Preparation of functional geopolymers from municipal solid waste incineration fly ash: An approach combining experimental and computational simulation studies - Mingyi Sun; Liping Ma; Quxiu Dai; Jie Yang; Longgui Xie; Yao Hu; Li Duan; Xiang Yan; Guanyun Zhou; Linglong Zeng; Lan Shao; Bo Hu; et al. (Journal of Environmental Management, 2024)

Bioaugmented ensiling of sweet sorghum with Pichia anomala and cellulase and improved enzymatic hydrolysis of silage via ball milling - Haiwei Ren; Jinlian Li; Yuanyuan Lan; Nana Lu; Hui Tian; Jinping Li; Zhiping Zhang; Lianhua Li; Yongming Sun; Yi Zheng (Journal of Environmental Management, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Enhanced glutathione production protects against zearalenone-induced oxidative stress and ferroptosis in female reproductive system - Wei Fu; Chao Dai; Zifeng Ma; Qiao Li; Daoliang Lan; Changpo Sun; Xin Wu; Jian Li; Shujin Wang (Food and Chemical Toxicology, 2024)

Selective membrane capacitive deionization for superior lithium recovery - Jiangju Si; Chenrui Xue; Shun Li; Linchao Yang; Weiwei Li; Jie Yang; Jihong Lan; Ningbo Sun (Desalination, 2024)

Thermoelectric properties of Bi2Te3 films with low-angle grain boundaries formed through high pulse current density - Mingdi Lan; Shang Sun; Shiying Liu; Guojian Li; Xiao Sun; Qiang Wang (Chemical Engineering Journal, 2024)

River incision and fracture density controls on the style and pattern of slope failure on the northeastern Tibetan Plateau - Xueliang Wang; John J. Clague; Shengwen Qi; Hengxing Lan; Lihui Li; Wenxin Fang; JuanJuan Sun; Junfei Wang (Natural Hazards, 2024)

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Porcine delta coronavirus inhibits NHE3 activity of porcine intestinal epithelial cells through miR-361–3p/NHE3 regulatory axis - Zehong Huang; Mengjing Cao; Haoqian Fan; Yuan Sun; Tian Lan; Jingyun Ma; Qianniu Li (Veterinary Microbiology, 2024)

Sulfur atom-directed metal–ligand synergistic catalysis in zirconium/hafnium-oxo clusters for highly efficient amine oxidation - Sheng-Nan Sun; Qian Niu; Jiao-Min Lin; Li-Ling He; Jing-Wen Shi; Qing Huang; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Discovery of bioactive polycyclic polyprenylated acylphloroglucinols with adamantine/homoadamantane skeletons from Hypericum wilsonii - Bo Tao; Yongqi Li; Zhengyi Shi; Yulin Duan; Yi Guo; Xinye Huang; Jie Li; Yeting Zhang; Ming Chen; Fei Song; Xueqi Lan; Weiguang Sun; et al. (Phytochemistry, 2024)

Conversion mechanism for solving the end-stop problem of hydraulic power take-off system for wave energy - Dahai Zhang; Chenglong Li; Ran Bi; Xin Huang; Zhiwei Sun; Tianlong Lan; Yuankui Wang; Ting Huang; Peng Qian (Ocean Engineering, 2024)

The hysteresis damage of cold exposure on tissue and transcript levels in mice - Jing Zhang; Shiwan You; Lan Yu; Yuling Zhang; Zuoping Li; Na Zhao; Bo Zhang; Lihua Kang; Shiguo Sun (Journal of Thermal Biology, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

Effects of limited enzymatic hydrolysis and polysaccharide addition on the physicochemical properties of emulsions stabilized with duck myofibrillar protein under low-salt conditions - Shufeng He; Mengmeng Li; Yangying Sun; Daodong Pan; Changyu Zhou; Hangzhen Lan (Food Chemistry, 2024)

Preparation of chitosan/citral forward osmosis membrane via Schiff base reaction with enhanced anti-bacterial properties - Lei Wu; Xiaolu Gong; Cong Ma; Lan Xu; Ming Li; Chen Lyu; Nan Sun (Chemosphere, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Enhanced metabolic resistance mechanism endows resistance to metamifop in Echinochloa crus-galli (L.) P. Beauv. - Penglei Sun; Liangliang Niu; Xianmin Lan; Haiyan Yu; Hailan Cui; Jingchao Chen; Xiangju Li (Pesticide Biochemistry and Physiology, 2023)

Synthesis of a double type-II CdS/Zn2In2S5/g-C3N4 heterojunction photocatalyst for the photodegradation of tetracycline under visible light - Yuzhen Li; Zhaoxin Sun; Sufang Wang; Runbin Duan; Shaojie Wang; Shuo Li; Borong Lan; Lizhen Gao (Journal of Environmental Chemical Engineering, 2023)

Correlation between microbial community succession and flavor substances during fermentation of Yongchuan Douchi - Lin Lan; Jingxin Wang; Shengyu Wang; QiaoLing He; Ruilin Wei; Zaixing Sun; Shuhua Duan; Yufeng Li (Food Bioscience, 2023)

Dysregulation of immunity by cigarette smoking promotes inflammation and cancer: A review - Yubin Liu; Lan Lu; Huan Yang; Xu Wu; Xinyue Luo; Jing Shen; Zhangang Xiao; Yueshui Zhao; Fukuan Du; Yu Chen; Shuai Deng; Chi Hin Cho; et al. (Environmental Pollution, 2023)

Multifunctional graphene/Ag hydrogel with antimicrobial and catalytic properties for efficient solar-driven desalination and wastewater purification - Lin Lin; Wenrui Wang; Danyi Li; Siyi Xu; Ying Sun; Linfan Li; Kai Fan; Chenyang Xing; Lan Zhang; Jihao Li (Chemical Engineering Journal, 2023)

Formation and evolution of a loess sinkhole in the southern Chinese Loess Plateau - Junli Ren; Wei Gong; Cheng Xue; Peng Cheng; Ting Li; Li Ai; Huan Jiang; Xingxing Liu; Yukun Fan; Jianghu Lan; Liangcheng Tan; Youbin Sun (CATENA, 2023)

Characterization of polycyclic aromatic hydrocarbons (PAHs) in atmospheric particles (PM2.5) in the North China Plain using positive-ion atmospheric pressure photoionization (APPI) coupled with fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) - Hao Sun; Li Wang; Xinyuan Kang; Zilan Wu; Haoran Yu; Ren'an Wu; Lan Yao; Jianmin Chen (Atmospheric Environment, 2023)

α-LA attenuates microcystin-LR-induced hepatocellular oxidative stress in mice through Nrf2-mediated antioxidant and detoxifying enzymes - Jun Bai; Chaoyun Chen; Yaochuan Sun; Shangchun Li; Renjiang He; Qingbi Zhang; Qian Sun; Yu Huang; Ailin Tan; Li Yuan; Yinxing Huang; Yuanyuan Lan; et al. (Toxicon, 2023)

Comprehensive analysis of nanoplastic effects on growth phenotype, nanoplastic accumulation, oxidative stress response, gene expression, and metabolite accumulation in multiple strawberry cultivars - Chendong Sun; Xiaofang Yang; Qijuan Gu; Guihua Jiang; Lan Shen; Jiayan Zhou; Long Li; Hexiu Chen; Guofang Zhang; Yuchao Zhang (Science of The Total Environment, 2023)

The formation of proto-austronesians: insights from a revised phylogeography of the paternal founder lineage - Hui-Xin Yu; Xian-Peng Zhang; Yun Bai; Kai-Jun Liu; Hui Li; Yong-Lan Li; Jin Sun; Lan-Hai Wei (Molecular Genetics and Genomics, 2023)

Essential metal mixtures exposure and NAFLD: A cohort-based case-control study in northern Chinese male adults - Di Zhang; Shouling Wu; Yanqi Lan; Shuohua Chen; Yanhong Wang; Yuanyuan Sun; Ying Lu; Wei Liao; Li Wang (Chemosphere, 2023)

Abietane diterpenoids with anti-inflammatory activities from Callicarpa bodinieri - Yue Sun; Hong-Ying Yang; Pei-Zhi Huang; Lan-Jun Zhang; Wei-Jiao Feng; Ya Li; Kun Gao (Phytochemistry, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Identifying priority areas for freshwater supply conservation integrating multi-scale freshwater flows - Yan Xu; Hailian Lan; Benyao Wang; Xian Zhao; Dehuan Li; Yixuan Yang; Yujing Xie; Wei Sun (Journal of Environmental Management, 2023)

Polyurethane sponge loading improves the suspension of magnetic materials without affecting the Pb(Ⅱ) adsorption - Ruifeng Li; Guihong Lan; Yongqiang Liu; Qiao Sun; Bin Luo; Ming Zhang; Haiyan Qiu; Bo Xu; Chunping Deng (Journal of Environmental Chemical Engineering, 2023)

Multifunctional 2D-3D heterogeneous MXene@ZIF-8 coated cotton/lyocell blended fabrics for fire protection, motion detection and UV-resistance - Lan Ding; Ling Sun; Ziwei Wang; Di Li; Qiuyan Zhang; Xiaohui Liu; Yuanlin Ren; Yuesheng Li (Chemical Engineering Journal, 2023)

Association Between Blood Calcium, Magnesium, and Non-alcoholic Fatty Liver Disease in Adults: a Cohort-Based Case-Control Study - Chenlu Yang; Shouling Wu; Yanqi Lan; Shuohua Chen; Di Zhang; Yanhong Wang; Yuanyuan Sun; Wei Liao; Li Wang (Biological Trace Element Research, 2023)

Factors impacting the behavior of phytoremediation in pesticide-contaminated environment: A meta-analysis - Fang Jia; Yue Li; Qian-nan Hu; Lan Zhang; Lian-gang Mao; Li-zhen Zhu; Hong-yun Jiang; Xin-gang Liu; Yan Sun (Science of The Total Environment, 2023)

Dual active sites over Cu-ZnO-ZrO2 catalysts for carbon dioxide hydrogenation to methanol - Xiucheng Sun; Yifei Jin; Zaizhe Cheng; Guojun Lan; Xiaolong Wang; Yiyang Qiu; Yanjiang Wang; Huazhang Liu; Ying Li (Journal of Environmental Sciences, 2023)

Genetic characterization of Sus scrofa papillomavirus type 1 from domestic pigs in Guangxi Province, China - Yuying Li; Xinyu Zhang; Chenchen Zhao; Xiaoxiao Lei; Haixin Huang; Yaokai Shi; Chengkai Li; Jingshan Bi; Wenchao Sun; Tian Lan; Min Zheng (Brazilian Journal of Microbiology, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Mixed farming of rice and millets became the primary subsistence strategy 6400 years ago in the western Huanghuai Plain of Central China: New macrofossil evidence from Shigu - Yuzhang Yang; Miaomiao Yang; Binggui Sun; Weiya Li; Zhijie Cheng; Ling Yao; Wanli Lan; Xin Zhou; Juzhong Zhang (Archaeological and Anthropological Sciences, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Effect of food matrix on rapid detection of Vibrio parahaemolyticus in aquatic products based on toxR gene - Darong Li; Jiayi Zhao; Weiqing Lan; Yong Zhao; Xiaohong Sun (World Journal of Microbiology and Biotechnology, 2023)

Epigenetic Regulation of Ferroptosis in Central Nervous System Diseases - Ting Lan; Ting Ting Sun; Chao Wei; Tian Cheng; Fei Yang; Jian-Nan Zhang; Qian Li (Molecular Neurobiology, 2023)

A novel photoelectrochemical strategy for sequence-spot bispecific analysis of N6-methyladenosine modification based on proximity ligation-triggered cascade amplification - Yan Li; Yumeng Sun; Weiguo Yang; Lan Yang; Mingli Su; Lichao Fang; Junsong Zheng; Ruo Yuan; Wenbin Liang (Analytica Chimica Acta, 2023)

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

Insoluble dietary fibers from Lentinus edodes stipes improve the gel properties of pork myofibrillar protein: A water distribution, microstructure and intermolecular interactions study - Weiwei Lu; Di Wu; LiMei Wang; Geyao Song; Rongshuo Chi; Jing Ma; Zhenshun Li; Lan Wang; Weiqing Sun (Food Chemistry, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

Phase-change material cooling blanket: A feasible cooling choice during transport after exercise-induced hyperthermia - Xin Wang; Xueyi Shang; Xin Li; Shuyuan Liu; Bin Lai; Lizhi Ma; Ying Sun; Lan Ma; Bo Ning; Yan Li; Qian Wang (Journal of Thermal Biology, 2023)

Extracellular biomineralization of uranium and its toxicity alleviation to Bacillus thuringiensis X-27 - Ting Zhu; Qian Zeng; Changsong Zhao; Yufeng Wen; Shangqing Li; Feize Li; Tu Lan; Yuanyou Yang; Ning Liu; Qun Sun; Jiali Liao (Journal of Environmental Radioactivity, 2023)

Anti-inflammatory activities of triterpenoids from Euphorbia humifusa Willd - Pei-Zhi Huang; Hong-Ying Yang; Lan-Jun Zhang; Yue Sun; Ya Li; Kun Gao (Phytochemistry Letters, 2023)

Mainstream wastewater treatment by polyaluminium ferric chloride (PAFC) flocculation and nitritation-denitritation membrane aerated biofilm reactor (MABR) - Ming Li; Longzhi Liu; Zhiye Sun; Boyang Hu; Xinglin Li; Meichao Lan; Hong Guo; Baoan Li (Journal of Water Process Engineering, 2023)

Mxene regulates the stress of perovskite and improves interface contact for high-efficiency carbon-based all-inorganic solar cells - Yuan Xu; Fengli Liu; Ruoshui Li; Yu Jing; Qi Chen; Xia Chen; Chunyan Deng; Zhenbo Du; Weihai Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2023)

Source apportionment of heavy metals in soils around a coal gangue heap with the APCS-MLR and PMF receptor models in Chongqing, southwest China - Jie Ma; Zhi-jie Shen; Sheng-lan Wang; Li Deng; Jing Sun; Ping Liu; Ze-lei She (Journal of Mountain Science, 2023)

CO2 emission reduction pathways of iron and steel industry in Shandong based on CO2 emission equity and efficiency - Bingying Lan; Ke Dong; Li Li; Yalin Lei; Sanmang Wu; Ershi Hua; Ruyi Sun (Resources Policy, 2023)

Effects of different cooking treatments on the sensory qualities and pigmented phytochemicals of carrots - Shihan Bao; Xinjie Li; Tian Lan; Jiaqi Wang; Yayun Hu; Xiangyu Sun; Tingting Ma (Food Chemistry, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Liquid flow and breakage behaviors of two liquid jets impacting on the wire mesh with different impinging angles - Zhong-Bo Sun; Hai-Long Liao; Li-Hua Wang; Lan Jiang; Xin Zhang; Bao-Ju Wang; Guang-Wen Chu; Yong Luo (Chemical Engineering Journal, 2023)

Fe3+-enhanced zero valent iron/peroxymonosulfate (ZVI/PMS) process for the transformation of iopamidol during coagulation and reduction of iodinated disinfection by-products - Yuanxiang Mao; Yifei Wu; Xiaoli Lu; Caiping Sun; Chenglin Li; Yuzhe Chen; Lei Jiang; Qiushi Shen; Qian Zhang; Caocong Liu; Jialiang Liang; Huiyu Dong; et al. (Chemical Engineering Journal, 2023)

Functional trait space and redundancy of plant communities decrease toward cold temperature at high altitudes in Southwest China - Lan Zhang; Xiaojuan Liu; Zhenhua Sun; Wensheng Bu; Franca J. Bongers; Xiaoyang Song; Jie Yang; Zhenkai Sun; Yin Li; Shan Li; Min Cao; Keping Ma; et al. (Science China Life Sciences, 2023)

Influences of Two Plant Growth Regulators on the Fruit Quality of the ‘Crimson Seedless’ Grapes - Lan Li; Weijiao Yan; Huidong Yao; Hui Li; Xizhi Guo; Dawei Cheng; Junli Sun; Jinyong Chen (Journal of Plant Growth Regulation, 2023)

Geographic distribution pattern and ecological niche differentiation of endangered Opisthopappus in Taihang Mountains - Li Liu; Hao Zhang; En Zang; Qiyang Qie; Shan He; Weili Hao; Yafei Lan; Zhixia Liu; Genlou Sun; Yiling Wang (Brazilian Journal of Botany, 2023)

Immunoprotection effects of chicken egg yolk immunoglobulins (IgY) against Aeromonas veronii infection in Sinocyclocheilus grahami - Yunkun Li; Bangzhuo Huang; Shijie Sun; Nanyi Liu; Yunqi Li; Minwen Lan; Xiaoai Wang; Yuanwei Zhang; Anli Wu; Shiyong Yang; Jiayun Wu; Xianyin Zeng; et al. (Aquaculture, 2023)

A ca. 290 Ma hydrothermal calcite in Cambrian dolostone - Zhongwu Lan; Shitou Wu; Fangyue Wang; Bo Liu; Kaibo Shi; Jing Sun; Rong Cao; Xian-Hua Li (Marine and Petroleum Geology, 2023)

Amorphous antimony sulfide nanoparticles construct multi-contact electron transport layers for efficient carbon-based all-inorganic CsPbI2Br perovskite solar cells - Yu Jing; Xiao Liu; Yuan Xu; Meng Zhang; Ruoshui Li; Shibo Wang; Zhongliang Yan; Weihai Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2023)

Visualization on the meso-scale particle flow in turbulent fluidized bed reactors with lower H0/D ratios via image processing - Chengxiu Wang; Zhihui Li; Zeneng Sun; Xingying Lan; Jinsen Gao; Mao Ye; Jesse Zhu (Chemical Engineering Journal, 2023)

Hemodynamic effects of intravenous bolus injection of iopromide 370 twice in abdominal contrast-enhanced CT and coronary CTA dual-site sequential examinations - Lingru Wang; Haiyan Qiu; Lan Chen; Heng Liu; Junling Liu; Ying Yang; Yueting Sun; Yang Deng; Heng Liu; Xue Li (Medical & Biological Engineering & Computing, 2023)

Characterization and genomic analysis of JC01, a novel bacteriophage infecting Cronobacter sakazakii - Jie Jiang; Guanda Lan; Jinghua Li; Jun Yu; Honglan Huang; Yanbo Sun; Cuiting Xu; Dandan Liu; Yunwei Gong; Chunyan Zhao (Archives of Virology, 2023)
The lytic bacteriophage JC01 was isolated using a strain of Cronobacter sakazakii previously isolated from powdered infant formula (PIF). The complete genome sequence of phage JC01 was determined. The double-stranded DNA genome of phage JC01 is composed of 61,736 bp with a G + C content of 58.9%, and it contains 76 putative open reading frames (ORFs) without any tRNA genes. The predicted ORFs were classified into functional groups, including DNA manipulation, transcription, phage packaging, phage structure, host lysis, and hypothetical proteins. Based on overall nucleotide sequence comparisons, calculation of phage intergenomic similarities, and phylogenetic analysis, JC01 appears to be a novel bacteriophage infecting C. sakazakii .

Correction to: Behavioral and brain functional characteristics of children with attention-defcit/hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

Behavioral and brain functional characteristics of children with Attention-Deficit/Hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

New cytotoxic ergosterols from a plant-associated fungus Colletotrichum magnisporum - Yanqi Hao; Lan Wei; Li Li; Yanlei Wang; Ning Li; Yingni Pan; Yi Sun (Natural Product Research, 2022)

A urinary proteomic landscape of COVID-19 progression identifies signaling pathways and therapeutic options - Yuntao Liu; Lan Song; Nairen Zheng; Jinwen Shi; Hongxing Wu; Xing Yang; Nianci Xue; Xing Chen; Yimin Li; Changqing Sun; Cha Chen; Lijuan Tang; et al. (Science China Life Sciences, 2022)

Complete mitochondrial genomes of Thyreophagus entomophagus and Acarus siro (Sarcoptiformes: Astigmatina) provide insight into mitogenome features, evolution, and phylogeny among Acaroidea mites - Yu Fang; Mingzhong Sun; Ying Fang; Zetao Zuo; Luyao Liu; Lingmiao Chu; Lan Ding; Caixiao Hu; Feiyan Li; Renrui Han; Xingquan Xia; Shulin Zhou; et al. (Experimental and Applied Acarology, 2022)

Phyllosphere fungal communities of rubber trees exhibited biogeographical patterns, but not bacteria - Yaqing Wei; Guoyu Lan; Zhixiang Wu; Bangqian Chen; Fei Quan; Mingmei Li; Shuqing Sun; Haonan Du (Environmental Microbiology, 2022)
Summary Phyllosphere microbiomes play an essential role in maintaining host health and productivity. Still, the diversity patterns and the drivers for the phyllosphere microbial community of the tropical cash crop Rubber tree ( Hevea brasiliensis ) – are poorly understood. We sampled the phyllosphere of field‐grown rubber trees in South China. We examined the phyllosphere bacterial and fungal composition, diversity and main drivers of these microbes using the Illumina® sequencing and assembly. Fungal communities were distinctly different in different climatic regions (i.e. Xishuangbanna and Hainan Island) and climatic factors, especially mean annual temperature, and they were the main driving factors of foliar fungal communities, indicating fungal communities showed a geographical pattern. Significant differences of phyllosphere bacterial communities were detected in different habitats (i.e. endophytic and epiphytic). Most of the differences in taxa composition came from Firmicutes spp., which have been assigned as nitrogen‐fixing bacteria. Since these bacteria cannot penetrate the cuticle like fungi, the abundant epiphytic Firmicutes spp. may supplement the deficiency of nitrogen acquisition. And the main factor influencing endophytic bacteria were internal factors, such as total nitrogen, total phosphorus and water content of leaves. External factors (i.e. climate) were the main driving force for epiphytic bacteria community assembly. Our work provides empirical evidence that the assembly of phyllosphere bacterial and fungal differed, which creates a precedent for preventing and controlling rubber tree diseases and pests and rubber tree yield improvement.

Predicting acupuncture efficacy for functional dyspepsia based on routine clinical features: a machine learning study in the framework of predictive, preventive, and personalized medicine - Tao Yin; Hui Zheng; Tingting Ma; Xiaoping Tian; Jing Xu; Ying Li; Lei Lan; Mailan Liu; Ruirui Sun; Yong Tang; Fanrong Liang; Fang Zeng (EPMA Journal, 2022)

Bone Marrow Mesenchymal Stem Cells Exert Protective Effects After Ischemic Stroke Through Upregulation of Glutathione - Xiao-Yan Lan; Zheng-Wu Sun; Gui-Lian Xu; Cheng-Yan Chu; Hua-Min Qin; Shen Li; Xin Geng; Peng Gao; Johannes Boltze; Shen Li (Stem Cell Reviews and Reports, 2022)

Handelin extends lifespan and healthspan of Caenorhabditis elegans by reducing ROS generation and improving motor function - Huijie Zhang; Jiawei Qin; Xinqiang Lan; Weirong Zeng; Jing Zhou; Tian-E Huang; Wan-Li Xiao; Qi-Quan Wang; Sujiao Sun; Weiting Su; Wenhui Nie; Shan Yang; et al. (Biogerontology, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Assessing relative density of carbonate granular soil via dynamic cone penetration field and model tests - Lan Lin; Sa Li; Liqiang Sun; Tingting Li; Jiangsong Yin (Marine Georesources & Geotechnology, 2021)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Whole Genomic DNA Methylation Profiling of CpG Sites in Promoter Regions of Dorsal Root Ganglion in Diabetic Neuropathic Pain Mice - Wen Chen; Ting Lan; Qingyu Sun; Yurui Zhang; Danmin Shen; Tingting Hu; Jing Liu; Yingzi Chong; Peipei Wang; Qian Li; Weihua Cui; Fei Yang (Journal of Molecular Neuroscience, 2021)

Culture Enrichment Combined With Long-Read Sequencing Facilitates Genomic Understanding of Hadal Sediment Microbes - Huan Wang; Meng Wang; Shen Fan; Jie Lu; Yi Lan; Menggong Li; Jiangyan Li; Rulong Liu; Jin Sun; Jiasong Fang; Pei-Yuan Qian; Yu-Zhong Zhang; et al. (Frontiers in Marine Science, 2021)
Culture enrichment was developed to discover the uncharted microbial species in the environmental microbiota. Yet this strategy has not been widely used to study microbes of deep-sea environments. Here, we report the cultivation and metagenomic analysis of oceanic sediment microbiota collected from 6,477 m deep in the Mariana Trench. The sediment samples were cultured anaerobically in the laboratory for 4 months, before being subjected to full-length 16S rRNA gene sequencing using the PacBio technique and metagenome sequencing using both the Illumina and Oxford Nanopore techniques. The 16S rRNA gene analyses revealed 437 operational taxonomic units specific to the cultured microbes, despite the lower diversity of the cultured microbiota in comparison with the original. Metagenome analyses revealed the prevalence of functions related to respiration, energy production, and stress response in the cultured microbes, suggesting these functions may contribute to microbial proliferation under laboratory conditions. Binning of the assembled metagenome contigs of the cultured microbiota generated four nearly complete genomes affiliated to yet unclassified species under the genera Alcanivorax , Idiomarina , Sulfitobacter , and Erythrobacter . Excepting Alcanivorax , the other three genera were almost undetectable in the original samples and largely enriched in the cultured samples. The four genomes possessed a variety of genes for carbohydrate utilization and nitrite reduction, pointing to an ability to respire diverse carbon sources using nitrite as the final electron acceptor. Taken together, the findings suggest that a combination of culture enrichment and long-read sequencing is an ideal way to mine novel microbial species in the hadal environment, particularly species that are rare in their native environmental niches, and thus expand our understanding of the hadal microbial diversity and function.

A new triterpenoid and other constituents with cytotoxic activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Lan Jin; Yanqiu Qi; Lihua Cao; Wei Zhou; Gao Li (Natural Product Research, 2021)

Association between population density and infection rate suggests the importance of social distancing and travel restriction in reducing the COVID-19 pandemic - Heliang Yin; Tong Sun; Lan Yao; Yan Jiao; Li Ma; Lin Lin; J Carolyn Graff; Lotfi Aleya; Arnold Postlethwaite; Weikuan Gu; Hong Chen (Environmental Science and Pollution Research, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Long-Term Variability of Piscivorous Fish in China Seas Under Climate Change With Implication for Fisheries Management - Dan Liu; Yongjun Tian; Shuyang Ma; Jianchao Li; Peng Sun; Zhenjiang Ye; Caihong Fu; Kuowei Lan; Shijie Zhou (Frontiers in Marine Science, 2021)
Due to persistent fishing expansion in the China Seas over the past six decades, fisheries resources have been over-exploited; as a result, exploited fish have become smaller in size and younger in age. Marine piscivorous fish constituted a large portion of Chinese fisheries catch, long-term variability of which has rarely been investigated despite intense fishing pressure and climate change. In this study, we attempt to identify their responses to climate change and fishing activities and to provide scientific basis for sustainable exploitation of these resources. Seven taxa from pelagic to demersal species inhabiting either cold-water or warm-water were selected to represent the piscivorous fish assemblage in the China Seas. Total catch of these piscivorous fish in the China Seas increased during the early 1990s, stabilizing around 1.2 million tons after 1997. Principal component analysis (PCA) showed evident interannual-decadal variabilities in the catch of these fish with step changes around 1985/86 and 1997/98. Individual taxa, however, showed different trends in catches with sharks, rays, and lizardfishes manifesting downward trends while Pacific cod, eels, and hairtail increasing. Common dolphinfish and Japanese-Spanish mackerel increased largely in the 1990s but declined slightly during the 2000s. Although there were temporal overlaps between climate change and fishing variabilities, results of gradient forest analyses indicated that fishing effort imposed the most important influence on piscivorous fish. And among all climate variables explored in this study, sea surface temperature (SST) especially that of the East China Sea, had greatest impacts on variations in piscivorous fish catch, which may have been gradually exacerbated by the continued high fishing intensity. In addition, significant changes were identified in the life history traits in the species we evaluated, such as reduced average body sizes and truncated age compositions, strongly indicating the effect of fishing. We therefore advocate precautionary fishery practices under climate change.

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

First detection and complete genome analysis of the Lyon IARC polyomavirus in China from samples of diarrheic cats - Yuying Li; Haixin Huang; Tian Lan; Wei Wang; Jie Zhang; Min Zheng; Liang Cao; Wenchao Sun; Huijun Lu (Virus Genes, 2021)

Molecular characterization of structural protein genes of dengue virus serotype 1 epidemic in Yunnan, Southwest China, in 2018 - Qingping Lan; Yun Shu; Linhao Li; Xiyun Shan; Dehong Ma; Tingting Li; Xiaodan Wang; Yue Pan; Junying Chen; Juan Zhang; Pinghua Liu; Qiangming Sun (Archives of Virology, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Synthesis and antitumor effects of a new class of 1,2,4-triazole derivatives - Zheng Wu; Xin Li; Chun-Lan Chi; Lu Xu; Yong-Yue Sun; Bao-Quan Chen (Medicinal Chemistry Research, 2021)

Could urinary ACE2 protein level help identify individuals susceptible to SARS-CoV-2 infection and complication? - Xiaotian Ni; Changqing Sun; Yaping Tian; Yanjie Huang; Tongqing Gong; Lan Song; Xing Yang; Kai Li; Nairen Zheng; Jianping Wang; Hongxing Wu; Ruoxian Zhang; et al. (Science China Life Sciences, 2020)

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Neuronal Activity in the Cerebellum During the Sleep-Wakefulness Transition in Mice - Li-Bin Zhang; Jie Zhang; Meng-Jia Sun; Hao Chen; Jie Yan; Fen-Lan Luo; Zhong-Xiang Yao; Ya-Min Wu; Bo Hu (Neuroscience Bulletin, 2020)

Long-term influence of maize stover and its derived biochar on soil structure and organo-mineral complexes in Northeast China - Qiang Sun; Jun Meng; Binoy Sarkar; Yu Lan; Li Lin; Haifeng Li; Xu Yang; Tiexin Yang; Wenfu Chen; Hailong Wang (Environmental Science and Pollution Research, 2020)

1 H NMR-based metabonomics of the hypoglycemic effect of polysaccharides from Cordyceps militaris on streptozotocin-induced diabetes in mice - Xiao-Lan Shang; Li-Chao Pan; Yun Tang; You Luo; Zhen-Yuan Zhu; Hui-Qing Sun; Meng Meng; Yong-min Zhang (Natural Product Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Comparison of Al18F- and 68Ga-labeled NOTA-PEG4-LLP2A for PET imaging of very late antigen-4 in melanoma - Yongkang Gai; Lujie Yuan; Lingyi Sun; Huiling Li; Mengting Li; Hanyi Fang; Bouhari Altine; Qingyao Liu; Yongxue Zhang; Dexing Zeng; Xiaoli Lan (JBIC Journal of Biological Inorganic Chemistry, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Cell bioreactor culture of Orostachys cartilaginous A. Bor. and involvement of nitric oxide in methyl jasmonate-induced flavonoid synthesis - Yue-Jun Hao; Xi-Hua Cui; Jin-Rong Li; Xiao-Li An; Hao-Ding Sun; Xuan-Chun Piao; Mei-Lan Lian (Acta Physiologiae Plantarum, 2020)

The mechanism of resistance loss of the super rice varieties to rice blast - Bo Lan; Yingqing Q. Yang; Qiang Sun; Hongfan Chen; Yonghui Huang; Jian Chen; Xiangmin Li; Guanghua Huo (Journal of Plant Pathology, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Adventitious root cultures of Oplopanax elatus inhibit LPS-induced inflammation via suppressing MAPK and NF-κB signaling pathways - Wen Tian; Xuan-Mei Piao; Cheng-Ri Yin; Xiao-Long Jiang; Hao-Ding Sun; Xiao-Li An; Jun Jiang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Animal, 2019)

A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Linlin Du; Wenjuan Shi; Xuejuan Li; Ying Lan; Feng Sun; Yongjian Fan; Tong Zhou; Yijun Zhou (Australasian Plant Pathology, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

A female attractant for the blue gum chalcid, Leptocybe invasa (Hymenoptera: Eulophidae), from host plant (DH 201-2: Eucalyptus grandis × Eucalyptus tereticornis) - Tao Ma; Laijiao Lan; Na Lin; Lifei Zheng; Zhaohui Sun; Yizhen Li; Xiujun Wen (Arthropod-Plant Interactions, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Isolation, characterization, genomic sequencing, and GFP-marked insertional mutagenesis of a high-performance nitrogen-fixing bacterium, Kosakonia radicincitans GXGL-4A and visualization of bacterial colonization on cucumber roots - Shuaixin Sun; Yunpeng Chen; Jiejie Cheng; Qiongjie Li; Zhenchuan Zhang; Zhengliang Lan (Folia Microbiologica, 2018)

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

Unearthing the effects of personality traits on consumer’s attitude and intention to buy green products - Ying Sun; Shanyong Wang; Lan Gao; Jun Li (Natural Hazards, 2018)

Cystatin C Induces Insulin Resistance in Hippocampal Neurons and Promotes Cognitive Dysfunction in Rodents - Lan Luo; Jinyu Ma; Yue Li; Zongkang Hu; Chengfeng Jiang; Hao Cai; Cheng Sun (Neuroscience Bulletin, 2018)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

Exclosure on CT-measured soil macropore characteristics in the Inner Mongolia grassland of northern China - Xia Hu; Yan-Li Lyu; Yong Liu; Xiao-Yan Li; Zhen-Ting Sun; Zong-Chao Li; Ya-Qian Cheng; Lan-Lan Guo; Lian-You Liu (Journal of Soils and Sediments, 2018)

PHP14 regulates hepatic stellate cells migration in liver fibrosis via mediating TGF-β1 signaling to PI3Kγ/AKT/Rac1 pathway - Anjian Xu; Yanmeng Li; Wenshan Zhao; Fei Hou; Xiaojin Li; Lan Sun; Wei Chen; Aiting Yang; Shanna Wu; Bei Zhang; Jingyi Yao; Huan Wang; et al. (Journal of Molecular Medicine, 2018)

Two new protostane-type triterpenoids from Alisma orientalis - Xiu-Lan Xin; Xin-Yu Zhao; Xiao-Kui Huo; Xiang-Ge Tian; Cheng-Peng Sun; Hou-Li Zhang; Yan Tian; Yong Liu; Xun Wang (Natural Product Research, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

AnkG hemizygous mice present cognitive impairment and elevated anxiety/depressive-like traits associated with decreased expression of GABA receptors and postsynaptic density protein - Cui Liu; Ling Zhang; Jie Wu; Xiaolong Sui; Yanfeng Xu; Lan Huang; Yunlin Han; Hua Zhu; Yanhong Li; Xiuping Sun; Chuan Qin (Experimental Brain Research, 2017)

The oxidative DNA damage response: A review of research undertaken with Tsinghua and Xiangya students at the University of Pittsburgh - Arthur S. Levine; Luxi Sun; Rong Tan; Ying Gao; Lu Yang; Hao Chen; Yaqun Teng; Li Lan (Science China Life Sciences, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Molecular adaptation in the world's deepest‐living animal: Insights from transcriptome sequencing of the hadal amphipod Hirondellea gigas - Yi Lan; Jin Sun; Renmao Tian; Douglas H. Bartlett; Runsheng Li; Yue Him Wong; Weipeng Zhang; Jian‐Wen Qiu; Ting Xu; Li‐Sheng He; Harry G. Tabata; Pei‐Yuan Qian (Molecular Ecology, 2017)
The Challenger Deep in the Mariana Trench is the deepest point in the oceans of our planet. Understanding how animals adapt to this harsh environment characterized by high hydrostatic pressure, food limitation, dark and cold is of great scientific interest. Of the animals dwelling in the Challenger Deep, amphipods have been captured using baited traps. In this study, we sequenced the transcriptome of the amphipod Hirondellea gigas collected at a depth of 10,929 m from the East Pond of the Challenger Deep. Assembly of these sequences resulted in 133,041 contigs and 22,046 translated proteins. Functional annotation of these contigs was made using the go and kegg databases. Comparison of these translated proteins with those of four shallow‐water amphipods revealed 10,731 gene families, of which 5659 were single‐copy orthologs. Base substitution analysis on these single‐copy orthologs showed that 62 genes are positively selected in H. gigas , including genes related to β‐alanine biosynthesis, energy metabolism and genetic information processing. For multiple‐copy orthologous genes, gene family expansion analysis revealed that cold‐inducible proteins (i.e., transcription factors II A and transcription elongation factor 1) as well as zinc finger domains are expanded in H. gigas . Overall, our results indicate that genetic adaptation to the hadal environment by H. gigas may be mediated by both gene family expansion and amino acid substitutions of specific proteins.

Streptomyces gamaensis sp. nov., a novel actinomycete with antifungal activity isolated from soil in Gama, Chad - Shanshan Zhao; Lan Ye; Chongxi Liu; Adam Yacoub Abagana; Weiwei Zheng; Pengyu Sun; Jiansong Li; Wensheng Xiang; Xiangjing Wang (Antonie van Leeuwenhoek, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Gene expression signatures for phlegm-dampness constitution of Chinese medicine - Lingru Li; Juan Feng; Haiqiang Yao; Lan Xie; Yu Chen; Lingling Yang; Shujuan Hou; Shipeng Zhao; Ranran Sun; Yanling Wu; Tongtong Bai; Yingshuai Li; et al. (Science China Life Sciences, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Role of AMP-activated protein kinase α1 in 17α-ethinylestradiol-induced cholestasis in rats - Xiaojiaoyang Li; Runping Liu; Lan Luo; Linxi Yu; Xin Chen; Lixin Sun; Tao Wang; Phillip B. Hylemon; Huiping Zhou; Zhenzhou Jiang; Luyong Zhang (Archives of Toxicology, 2017)

Haplotypes of bovine FoxO1 gene sequence variants and association with growth traits in Qinchuan cattle - YUJIA SUN; JING XUE; WENJIAO GUO; MENJIAO LI; YONGZHEN HUANG; XIANYONG LAN; CHUZHAO LEI; CHUNLEI ZHANG; HONG CHEN (Journal of Genetics, 2016)

The destruction box is involved in the degradation of the NTE family proteins by the proteasome - Fei-Fei Huang; Ping-An Chang; Lan-Xi Sun; Wen-Zhen Qin; Li-Ping Han; Rui Chen (Molecular Biology Reports, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Assessing the clinical features of LGI1 antibody encephalitis - Pan-Pan Zhao; Ying Zhang; Lan Gao; Li Sun (Acta Neurologica Belgica, 2016)

A novel dual EGFR/HER2 inhibitor KU004 induces cell cycle arrest and apoptosis in HER2-overexpressing cancer cells - Chongchong Tian; Pingping Ding; Ziqiao Yuan; Han Li; Yanxia Zhao; Lan Sun; Qingming Guo; Zhenzhong Wang; Lixin Sun; Luyong Zhang; Zhenzhou Jiang (Apoptosis, 2015)

Analyzing the spatial patterns and drivers of ecosystem services in rapidly urbanizing Taihu Lake Basin of China - Junyong Ai; Xiang Sun; Lan Feng; Yangfan Li; Xiaodong Zhu (Frontiers of Earth Science, 2015)

Evidence for and characterization of nervous necrosis virus infection in Pacific cod (Gadus macrocephalus) - Ming-Guang Mao; Shi-Hui Wen; Alex Perálvarez-Marín; Hua Li; Jie-Lan Jiang; Zhi-Qiang Jiang; Xing Li; Hang Sun; Hui-Qian Lü (Archives of Virology, 2015)

Excitotoxicity Induced by Realgar in the Rat Hippocampus: the Involvement of Learning Memory Injury, Dysfunction of Glutamate Metabolism and NMDA Receptors - Tao-guang Huo; Wei-kai Li; Ying-hua Zhang; Jie Yuan; Lan-yue Gao; Yuan Yuan; Hui-lei Yang; Hong Jiang; Gui-fan Sun (Molecular Neurobiology, 2015)

Two novel polymorphisms of bovine SIRT2 gene are associated with higher body weight in Nanyang cattle - Xiaomei Sun; Mingxun Li; Dan Hao; Liushuai Hua; Xianyong Lan; Chuzhao Lei; Shenrong Hu; Xinglei Qi; Hong Chen (Molecular Biology Reports, 2015)

New serotypes of porcine teschovirus identified in Shanghai, China - Huan Sun; Han Gao; Molin Chen; Daoliang Lan; Xiuguo Hua; Chunyan Wang; Congli Yuan; Zhibiao Yang; Li Cui (Archives of Virology, 2015)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Production and in Vivo Antioxidant Activity of Zn, Ge, Se-enriched Mycelia by Cordyceps sinensis SU-01 - Lan Zheng; Long Hao; Hua Ma; Chengye Tian; Tong Li; Xinyi Sun; Mengshi Jia; Le Jia (Current Microbiology, 2014)

Allelic variants of PRNP in 16 Chinese local sheep breeds - Zouran Lan; Jinming Li; Chengyou Sun; Yutian Liu; Yonggang Zhao; Tianying Chi; Xiaojing Yu; Fangfang Song; Zhiliang Wang (Archives of Virology, 2014)

GRP78 expression and regulation in the mouse uterus during embryo implantation - PengFei Lin; YaPing Jin; XiangLi Lan; YanZhou Yang; Fenglei Chen; Nan Wang; Xiao Li; YuJie Sun; AiHua Wang (Journal of Molecular Histology, 2014)

Molecular detection of genogroup I and II picobirnaviruses in pigs in China - Molin Chen; Huan Sun; Daoliang Lan; Xiuguo Hua; Li Cui; Congli Yuan; Zhibiao Yang (Virus Genes, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Dishevelled-1 (Dvl-1) Protein: a Potential Participant of Oxidative Stress Induced by Selenium Deficiency - Han-dong Zhao; Mei-na Sun; Meng-di Li; Feng-lan Li; Hui Li (Biological Trace Element Research, 2014)

Elderly Patients and Coronary Heart Disease on Response to Treadmill Exercise Test - Jian-ling Sun; Guo-lan Gao; Ying Zhao; Yu-lian Gao; Li-juan Xiong; Ji-hong Guo; Xiao-ying Li (Cell Biochemistry and Biophysics, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

Microarray analysis of differentially expressed transcripts in porcine intestinal epithelial cells (IPEC-J2) infected with porcine sapelovirus as a model to study innate immune responses to enteric viruses - Daoliang Lan; Cheng Tang; Hua Yue; Huan Sun; Li Cui; Xiuguo Hua; Jian Li (Archives of Virology, 2013)

A Consensus Linkage Map Provides Insights on Genome Character and Evolution in Common Carp (Cyprinus carpio L.) - Xiaofeng Zhang; Yan Zhang; Xianhu Zheng; Youyi Kuang; Zixia Zhao; Lan Zhao; Chao Li; Li Jiang; Dingchen Cao; Cuiyun Lu; Peng Xu; Xiaowen Sun (Marine Biotechnology, 2013)

Spatial-temporal evolution pattern of agricultural productivity in northwestern sichuan plateau - Li Peng; Chun-jiang Su; Lian Sun; Ping Li; Yan Fang; Wei Liu; Xiao-lan Wang (Journal of Mountain Science, 2013)

Wogonin enhances antitumor activity of tumor necrosis factor-related apoptosis-inducing ligand in vivo through ROS-mediated downregulation of cFLIPL and IAP proteins - Lan Yang; Qiong Wang; Daoxia Li; Yuqiong Zhou; Xuelian Zheng; Hong Sun; Jiaqi Yan; Lin Zhang; Yong Lin; Xia Wang (Apoptosis, 2013)

Timing of formation and geological setting of low-sulphidation epithermal gold deposits in the continental margin of NE China - Jing-Gui Sun; Yong Zhang; Shi-Jiong Han; Lan-Jing Men; Yi-Xin Li; Peng Chai; Fan Yang (International Geology Review, 2013)

Determination of lignin in marine sediment using alkaline cupric oxide oxidation-solid phase extraction-on-column derivatization-gas chromatography - Ting Zhang; Xianguo Li; Shuwen Sun; Haiqing Lan; Peirui Du; Min Wang (Journal of Ocean University of China, 2013)

Comparing the Recalcitrance of Eucalyptus, Pine, and Switchgrass Using Ionic Liquid and Dilute Acid Pretreatments - Chenlin Li; Lan Sun; Blake A. Simmons; Seema Singh (BioEnergy Research, 2013)

Geology and ages of porphyry and medium- to high-sulphidation epithermal gold deposits of the continental margin of Northeast China - Shi-Jiong Han; Jing-Gui Sun; Ling-An Bai; Shu-Wen Xing; Peng Chai; Yong Zhang; Fan Yang; Lan-Jing Men; Yi-Xin Li (International Geology Review, 2013)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Lignin in marine environment and its analysis—A review - Xianguo Li; Ting Zhang; Shuwen Sun; Haiqing Lan; Tao Yu (Journal of Ocean University of China, 2012)

Genetic variations of ANGPTL6 gene and their associations with growth traits and slaughter traits in Qinchuan cattle - Ai-Min Li; Xian-Yong Lan; Xiao-Mei Sun; Yuan Gao; Wei Ma; Yun Ma; Hong Chen (Molecular Biology Reports, 2012)

Methylation pattern of oncogene HRAS gene promoter region and its clinical relevance to urocystic tumorigenesis - Xiao-Feng Sun; Lan Li; Xiu-Juan Li; Wei Shen (Molecular Biology Reports, 2012)

Alteration in methylation pattern of oncogene Akt1 promoter region in bladder cancer - Xiao-Feng Sun; Zhong-Yi Sun; Bo Pan; Lan Li; Wei Shen (Molecular Biology Reports, 2012)

Fetal exposure to bisphenol A affects the primordial follicle formation by inhibiting the meiotic progression of oocytes - Han-Qiong Zhang; Xi-Feng Zhang; Lian-Jun Zhang; Hu-He Chao; Bo Pan; Yan-Min Feng; Lan Li; Xiao-Feng Sun; Wei Shen (Molecular Biology Reports, 2012)

Bisphenol A exposure modifies methylation of imprinted genes in mouse oocytes via the estrogen receptor signaling pathway - Hu-He Chao; Xi-Feng Zhang; Bo Chen; Bo Pan; Lian-Jun Zhang; Lan Li; Xiao-Feng Sun; Qing-Hua Shi; Wei Shen (Histochemistry and Cell Biology, 2012)

Novel SNPs in the caprine stearoyl-CoA desaturase (SCD) and decorin (DCN) genes that are associated with growth traits in Chinese goat breeds - Zhongqi Chen; Jiajie Sun; Zhuanjian Li; Xianyong Lan; Chunlei Zhang; Yujiao Qu; Yanli Liu; Xingtang Fang; Chuzhao Lei; Hong Chen (Molecular Biology Reports, 2011)

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

Regulation of MMP-2 expression and activity by β-1,3-N-acetylglucosaminyltransferase-8 in AGS gastric cancer cells - Li Shen; Zhenhua Liu; Youbin Tu; Lan Xu; Xiaoya Sun; Shiliang Wu (Molecular Biology Reports, 2011)

Murine folliculogenesis in vitro is stage-specifically regulated by insulin via the Akt signaling pathway - Pan Zhang; Huhe Chao; Xiaofeng Sun; Lan Li; Qinghua Shi; Wei Shen (Histochemistry and Cell Biology, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

The 223A>G polymorphism of the leptin receptor gene and lipid-lowering efficacy of simvastatin in Chinese patients with coronary heart disease - Yan-Ming Sun; Lan-Feng Wang; Jia Li; Zhu-Qin Li; Wei Pan (European Journal of Clinical Pharmacology, 2009)

Rise and decline of ancient salt industry revealed by Na and Ca concentrations in sediments at Zhongba site, Chongqing - Cheng Zhu; Fengqing Jiang; Chunmei Ma; Weifeng Xu; Linyan Huang; Chaogui Zheng; Lan Li; Zhibin Sun (Journal of Geographical Sciences, 2008)

Characterization of cDNAs associated with lignification and their expression profiles in loquat fruit with different lignin accumulation - Lan Lan Shan; Xian Li; Ping Wang; Chong Cai; Bo Zhang; Chong De Sun; Wang Shu Zhang; Chang Jie Xu; Ian Ferguson; Kun Song Chen (Planta, 2008)

Expression Profiling and Validation of Potential Reference Genes During Paralichthys olivaceus Embryogenesis - Qiwang Zhong; Quanqi Zhang; Zhigang Wang; Jie Qi; Yanjie Chen; Shuo Li; Yeying Sun; Chunmei Li; Xun Lan (Marine Biotechnology, 2008)

Endogenous hydrogen peroxide in paraventricular nucleus mediating cardiac sympathetic afferent reflex and regulating sympathetic activity - Yang Yu; Ming-Kui Zhong; Jing Li; Xiu-Lan Sun; Gui-Qing Xie; Wei Wang; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2007)

Study on the expression and mutation of human telomeric repeat binding factor (hTRF1) in 10 malignant hematopoietic cell lines - Jie Sun; He Huang; Yuan-yuan Zhu; Jian-ping Lan; Jing-yuan Li; Xiao-yu Lai; Jian Yu (Journal of Zhejiang University-SCIENCE B, 2005)

Pretreatment of coking wastewater using anaerobic sequencing batch reactor (ASBR) - Bing Li; Ying-lan Sun; Yu-ying Li (Journal of Zhejiang University-SCIENCE B, 2005)

Vegetation changes of the Taihang Mountains since the last glacial - Xiao-lan Yang; Qing-hai Xu; He-ping Zhao; Wen-dong Liang; Li-ming Sun (Chinese Geographical Science, 2000)